TU Wien:Analysis UE (diverse)/Übungen SS19/Beispiel 171

Aus VoWi
Zur Navigation springen Zur Suche springen

Man beweise die Formel \sinh(x + y) = \sinh(x) \cosh(y) + \cosh(x) \sinh(y).

Hilfreiches[Bearbeiten]

\cosh(x) = \frac{e^x+e^{-x}}{2}

\sinh(x) = \frac{e^x-e^{-x}}{2}

Lösungsvorschlag[Bearbeiten]

\begin{align}
\sinh(x) \cosh(y) + \cosh(x) \sinh(y) &= \frac{e^{x}-e^{-x}}{2}\frac{e^{y}+e^{-y}}{2} + \frac{e^{x}+e^{-x}}{2}\frac{e^{y}-e^{-y}}{2} \\
&= \frac{(e^{x}-e^{-x})(e^{y}+e^{-y})+(e^{x}+e^{-x})(e^{y}-e^{-y})}{4} \\
&= \frac{e^{x+y}+e^{x-y}-e^{-x+y}-e^{-x-y}+e^{x+y}-e^{x-y}+e^{-x+y}-e^{-x-y}}{4} \\
&= \frac{e^{x+y}-e^{-x-y}+e^{x+y}-e^{-x-y}}{4} \\
&= \frac{2e^{x+y}-2e^{-x-y}}{4} \\
&= \frac{e^{x+y}-e^{-(x+y)}}{2} \\
&= \sinh(x + y)
\end{align}